Obligation of vaccination – legal and medical analysis - Fita, Michał; Król, Bartłomiej (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The authors analyze legal regulations regarding compulsory prophylactic vaccinations mentioned in the statue on preventing and fighting human infectious diseases. The analysis is concerned with constitutional, administrative, and criminal law, all devised in accordance with the present state of medical knowledge. Moreover, this work contains de lege ferenda postulates concerned with ways of ameliorating the execution of compulsory vaccinations – those postulates, according to the authors, would enhance the protection of human life and health. Introducing those changes would be crucial in face of the growing number of people who refuse to receive vaccinations or prevent their children from receiving them. Failing to recognize the importance of this situation may lead to future negative outcomes.